2020
DOI: 10.1097/cm9.0000000000001147
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA plasmacytoma variant translocation 1 linked to hypoxia-induced cardiomyocyte injury of H9c2 cells by targeting miR-135a-5p/forkhead box O1 axis

Abstract: Background Myocardial infarction occurs due to insufficient (ischemia) blood supply to heart for long time; plasmacytoma variant translocation 1 (PVT1) is a long non-coding RNAs (lncRNAs) involved in the pathogenesis of various diseases, including heart disease; However, few studies have explored its role. The present study evaluated the effects of lncRNA PVT1 on hypoxic rat H9c2 cells. Methods Hypoxic injury was examined by measuring cell viability and apoptosis by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
(31 reference statements)
0
2
0
Order By: Relevance
“… 37 Xu et al demonstrated that miR-135a-5p negatively regulated hypoxia-induced cardiomyocyte injury in H9c2 cells. 38 CENPB, a cell cycle-related gene, was reported to be differentially regulated in the heart tissue in serum-response factor null embryonic stem cells. 39 BCL9L is a nuclear co-activator in the Wnt/β-catenin pathway, which was shown to be associated with various cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Xu et al demonstrated that miR-135a-5p negatively regulated hypoxia-induced cardiomyocyte injury in H9c2 cells. 38 CENPB, a cell cycle-related gene, was reported to be differentially regulated in the heart tissue in serum-response factor null embryonic stem cells. 39 BCL9L is a nuclear co-activator in the Wnt/β-catenin pathway, which was shown to be associated with various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA is one of the ncRNA, which is thought to encode almost no proteins [1] . Although ncRNA plays a huge role in the process of life, participating in biological growth, [15] differentiation, [16] metabolism, [17] disease occurrence, [18–20] and other processes, its specific mechanism is still an unsolved mystery. Studies have shown that circRNA can participate in the occurrence of many autoimmune diseases and can regulate the course of diseases by regulating the body's immune response [21] and immune tolerance [22] .…”
Section: Discussionmentioning
confidence: 99%